2007
DOI: 10.2355/isijinternational.47.1255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti De-oxidation on Solidification and Post-solidification Microstructure in Low Carbon High Manganese Steel

Abstract: This paper investigates the effect of de-oxidation inclusions on micro-structure in low-carbon steels. Low carbon (0.07 wt%), high Mn (0.9 wt%) steel in a Al 2 O 3 or MgO crucible was deoxidized by adding either aluminum (0.05 wt%) or titanium (0.05, 0.03 or 0.015 wt%) in a 400 g-scale vacuum furnace, and cast in a Cu mold at cooling rates between 2.0-6.0 K/s.The oxide inclusions were identified as Al 2 O 3 (1-3 mm) in the Al-killed steel and Ti-Al-(Mg)-O (0.3-0.5 mm) in the Ti-killed steel. Oxide inclusion si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…[25][26][27][28] Results are summarized as follows. The following results are obtained by evaluating with the samples in Table 1.…”
Section: Effects Of Secondary Ti De-oxidation Particles Onmentioning
confidence: 99%
See 3 more Smart Citations
“…[25][26][27][28] Results are summarized as follows. The following results are obtained by evaluating with the samples in Table 1.…”
Section: Effects Of Secondary Ti De-oxidation Particles Onmentioning
confidence: 99%
“…Finally, the molten de-oxidized steel was poured into a water-cooled copper and stainless steel mold ( Inner size: 60×40×40 mm). The Al killed sample and a sample with no material added for deoxidation in the previous study 25) were used for comparison with the Ti-killed samples investigated in this study.…”
Section: De-oxidation and Castingmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, titanium oxide finely dispersed in steel and complex deoxidation including in titanium is considered to be effective for the above-mentioned purpose. 5) A determination of the equilibrium relationship between the oxide compounds in MgO-Al 2 O 3 -Ti 2 O 3 and molten iron is important to avoid Al 2 O 3 or MgO · Al 2 O 3 formation and for inclusion control. However, our previous work 6) is the only study that has reported on this and the equilibrium relationship between the deoxidation products and the composition of the solute elements in molten iron was investigated at 1 973 K. Therefore, in this study we investigated the equilibrium relationship between the oxide compounds in MgO-Al 2 O 3 -Ti 2 O 3 and molten iron at 1 873 K.…”
Section: Introductionmentioning
confidence: 99%